Talent-Based Leadership Mindset: A Catalyst for Talent Management and Retention in Indonesian Government Institutions - Listiyana Listiyana; Rita Alfin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Faced with increasingly intense competition, government institutions in Indonesia must adapt to retain quality talent. This study aims to examine the implementation of a talent-based leadership mindset as an innovative solution to enhance employee management and retention. Utilizing a qualitative approach, data were collected from 30 participants, including 10 agency leaders and 20 employees across the health, education, and public administration sectors. Findings indicate that most leaders recognize the significance of talent management in fostering a productive and innovative work environment. However, they encounter substantial challenges, including a lack of support from senior management and budget constraints, which often impede the execution of talent development programs. Employees reported tangible benefits from these initiatives, such as improved skills and motivation, although there was dissatisfaction regarding communication and transparency in the selection process. The implementation of a clear merit system emerged as a crucial factor in building employee trust in management. These findings underscore the necessity for regular evaluations of talent management policies to ensure sustainability and effectiveness. With the right approach, a talent-based leadership mindset can be pivotal in enhancing organizational performance and strengthening employee commitment.